Lipopolysaccharide and ARDS caused by new coronavirus infection: hypotheses and facts - I. A. Yatskov; V. A. Beloglazov; E. I. Ryapova (Медицинская иммунология)
This review presents data from the literature that provide insight into the role of the lipopolysaccharide (LPS) of the Gram-negative bacteria in pathogenesis of acute respiratory distress syndrome (ARDS) caused by the novel SARS-CoV-2 coronavirus infection. ARDS is a syndrome of severe respiratory failure, an acutely occurring diffuse inflammatory lesion of lung tissue that develops as a nonspecific reaction to various direct (aspiration, inhalation of toxic gases), and systemic (sepsis, polytrauma) damaging factors and leading to development of acute respiratory failure (ARF), due to impaired structure of the lung parenchyma, disturbances in vascular permeability, decreased area of ventilated lung tissue. ARDS from coronavirus infection appears to have worse outcomes than ARDS from other causes. Mortality from typical ARDS at the intensive care units and hospitals is 35.3% and 40.0%, respectively, while the lethality rates for COVID-19-associated ARDS, ranged from 26% to 61.5%. Among patients who underwent artificial ventilation of the lungs, the mortality rates can range from 65.7% to 94%. Risk factors for poor outcomes include, e.g., older age, presence of concomitant diseases such as hypertension, cardiovascular disease and diabetes mellitus; decreased number of lymphocytes, kidney injury, and increased D-dimer levels. Death with ARDS in COVID-19 occurs as a result of respiratory failure (53%), respiratory failure combined with heart failure (33%), myocardial damage and circulatory failure (7%), or death from an unknown cause. A large number of studies show that bacterial LPS is directly or indirectly involved in all pathogenetic links of ARDS caused by the SARS-CoV-2 virus, i.e., worsening the course of inflammatory lung diseases due to decreased level of angiotensin-converting enzyme 2 (ACE2); increasing generation of reactive oxygen species (ROS) via NADPH oxidase and subsequent inactivation of endothelial nitric oxide synthase (eNOS) and decreasing bioavailability of endothelial NO, thus leading to endothelial dysfunction; interacting with proteins of surfactants. SP-A and SP-D, promoting early destruction of the cellular monolayers and lowering surface tension, interact with soluble CD14 receptor, which also has a pro-inflammatory effect on epithelial and endothelial cells, leading to p38MAPK activation via TLR4 receptors, causing degradation of IêBá protein and subsequent translocation of p65 NF-êB into the nucleus, thus inducing transcription of IL-6 and adhesion molecules (ICAM-1, VCAM-1 and E-selectin), and, as shown by Petruk et al. (2020), causing direct binding to the viral S protein in combination with LPS, thus enhancing activation of nuclear factor-kappa B (NF-êB) in monocytic THP-1 cells and cytokine responses in mononuclear blood cells. These pathophysiological mechanisms require further in-depth study in order to understand the nature of changes that occur in the patients with new SARS-CoV-2 infection.